The perfect enemy: Maps, laws and sacrifice in the making of borders. (December 2013) - Mathur, Shubh
Borders are as much social and historical constructs as they are physical entities and run through geographies of the mind as well as over physical landscapes. It is in the borderlands that the narratives of nationhood begin to crumble, where they must be upheld through the full range of the techniques of domination. This paper examines three facets of the maintenance of borders of the post-Independence Indian nation-state. First, the creation of maps which are not mere instruments of utility or direct transcriptions of reality but rather a mixture of historical and political meanings and aspirations. Indian laws regarding maps and borders criminalize any representations of these which do not conform to the official version, even if used for purposes of political or academic discussion or debate. Such laws draw upon archaic, nineteenth century notions of sedition, and in seeking to uphold the "territorial integrity of the nation" serve only to highlight the arbitrary and contingent nature of national boundaries. Second, the laws of exception in effect in the borderlands of Kashmir and the northeast, which give the Indian military absolute power in dealing with the civilian population. In providing immunity from prosecution to military personnel accused of human rights violations, they serve to define the population of the borderlands as those who may be killed with impunity. Third, the maintenance of borders in the mind through public spectacles and displays such as the trial and sentencing of Afzal Guru, a Kashmiri Muslim executed by India, for his alleged role in the attack on the Indian parliament in December 2001. Anthropological writing on sacrifice, particularly the classic work of Hubert and Mauss, is relevant to understanding the meanings and consequences of this performance as it relates to the construction of the national community, its borders and its enemies.